CINTA RUMAH TUHAN: MENTORING BAGI WARGA GEREJA MILENIAL AGAR TERLIBAT DALAM PERIBADATAN - Pipit Hastari Budiarto; David Eko Setiawan; Steven Anugerah Ndruru; Limeani Zalukhu (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2021)
The current problem with the church in millenial church, that they abandoned worship or liturgy because the considered church liturgy to be a dull thing, and they also felt that church was unable to give them confidence ini the faith of Christ and the failure to maintain a proper upbringing of the church toward the millennial generation. The purpose of this research is to get an idea of the challenges that are. Faced by chruch leaders and gave advice on the efforts of chruch leaders to addressing the problems of millennial children throught mentoring in thr church. This research was the lebraries study with a qualitative approach. Based on these discussions, policycally it is recommended to be more innovative in introducing mentoring activities as the writer had suggested, it was carried out in the form of an activity, retreat, seminars or by giving their room to speaks.